Study of potential and development strategy of the Botolempangan Tourist Village in Maros Regency, Indonesia - Kattya Nusantari Putri; Muhammad Adam Asgar; Andi Nur Apung Massiseng (Agrikan: Jurnal Agribisnis Perikanan, 2020)
The growing public interest in travelling has become a different strength for the tourism industry currently. The existence of a person on a trip that can be shown on social media can be a force that indirectly becomes a promotional tool. The tourist village that is currently trending is a form of tourism which consists of natural tourism which is integrated with other tours, to provide a unique value compared to additional terms. The Karst area in Maros and Pangkep Regencies has the potential to be used as a tourist area, but currently, these karst areas have been widely used as raw material for the cement industry. One of the villages that has natural karst tourism in Maros Regency is the village of Botolempangan which has been planned by the village government as a tourism village because it has various unique natural resources that can become new income alternatives for the community, so it is essential to be developed as well as a reason to maintain the area. Karst which began to be eroded by industrial companies. The purpose of this study was to identify tourism potential and analyze the development strategy of the tourist village of Botolempangan. The research method used is observation, in-depth interviews and FGD. The analysis used is a descriptive qualitative analysis and SWOT analysis. Based on the results of the study, it shows that the village of Botolempangan has tourism potential in the form of natural karst tourism, cave tourism (leang), fisheries tourism, Sulawesi endemic monkeys, natural scenery, outbound, camping and educational tours. Based on the SWOT analysis, there are four strategies that can be carried out to develop the tourist village of Botolempangan, i.e. 1). The increased synergy between the government, universities and the community, especially managers in maximizing the supporting factors for the implementation of tourism villages 2). We are managing the Botolempangan karst area into a tourism village that is integrated with nature tourism, fisheries tourism, culinary tours and educational tours 3). Optimizing village budgets to improve tourist facilities and providing education for managers in supporting tourism 4). Increased promotions that prioritize the uniqueness of the region, facilities and the convenience of visiting through social media and partnerships with a local travel.